Observed Propagation Route of VLF Transmitter Signals in the Magnetosphere. Issue 7 (25th July 2018) - Zhang, Zhenxia; Chen, Lunjin; Li, Xinqiao; Xia, Zhiyang; Heelis, Roderick A.; Horne, Richard B.
Abstract: Signals of powerful ground transmitters at various places have been detected by satellites in near‐Earth space. The study on propagation mode, ducted or nonducted, has attracted much attentions for several decades. Based on the statistical results from Van Allen Probes (data from October 2012 to March 2017) and DEMETER satellite (from January 2006 to December 2007), we present the ground transmitter signals distributed clearly in ionosphere and magnetosphere. The observed propagation route in the meridian plane in the magnetosphere for each of various transmitters from the combination of DEMETER and Van Allen Probes data in nighttime is revealed for the first time. We use realistic ray tracing simulation and compare simulation results against Van Allen Probes and DEMETER observation. By comparison we demonstrate that the observed propagation route, with partial deviation from the field lines corresponding to ground stations, provides direct and clear statistical evidence that the nonducted propagation mode plays a main role, although with partial contribution from ducted propagation. The propagation characteristics of VLF transmitter signals in the magnetosphere are critical for quantitatively assessing their contribution to energetic electron loss in radiation belts. Plain Language Summary: The topic on signal propagation of ground‐based VLF transmitter in ionosphere and magnetosphere has attracted much attention in several decades. But the question about the propagation mode (ducted or nonducted) has not been answered definitely due to lacks of direct support from statistical satellite data. In this paper, the observed propagation route in the meridian plane in the magentosphere for each of various transmitter from the combination of DEMETER and Van Allen Probes data is revealed for the first time. Based on satellite observation and ray tracing simulation, we provide a clear and strong proof that the nonducted mode of transmitter signal plays a main role. The determination of the propagation mode will play a significant role in many fields, including the wave propagation model development and electron population adjustment as radiation belt remediation, which aims at lowering the damage of relativistic particles to the spacecraft and astronaut. Key Points: Satellite observation of the VLF ground‐based transmitter signals in the ionosphere and magnetosphere is presented Ray tracing simulation reproduces propagation routine of transmitter signals in the magnetosphere The observation and simulation both support that the nonducted mode is dominant